The Influence of Transformational and Transactional Leadership on Employee Performance Moderated by Social Support - Kurniawan, Rizal; Rumijati, Aniek; Roz, Kenny (Universitas Muhammadiyah Malang, 2023)
The purpose of this study is to determine whether there is an influence of transformational and transactional leadership styles on employee performance with social support as a moderating variable. This type of research uses quantitative methods with a sample size of 45 respondents. Sources of data obtained in this study from distributing questionnaires (primary data). The data analysis technique used in this study uses path analysis. The results of the study show that the transformational leadership style has a positive but not significant effect on employee performance. Likewise, the transactional leadership style has a positive but not significant effect on employee performance. Social support is not able to moderate the transformational leadership style on employee performance. In addition, social support is able to moderate the transactional leadership style on employee performance as a moderating variable.